APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) PADA PENANGANAN PASCAPANEN BAWANG MERAH (Allium ascalonicum L.) DARI PETANI DI KECAMATAN KINTAMANI SAMPAI DENPASAR - Pratama, I Putu Gede Angga Dian; Admadi, Bambang; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This research were aimed to 1) find out amount and kind of red onion (Allium Ascalonicum L.) distribution lines from farmers in Kintamani District Bangli regency area until Denpasar city, 2) to identify what factors are identified in the red onion (Allium Ascalonicum L.)  handler in Kintamani sub-district of Bangli Regency, and 3) know the impact of post-harvest handling when the distribution of red onion (Allium Ascalonicum L.)  loss from farmers in Bangli District Kintamani District. The research method used is survey method, with CSAM (Commodity System Assessment Method) application and using survey instrument in the form of questionnaires distributed to farmers, pegepul, merchants and red onion retailers in Kintamani sub-district to Denpasar. The were four distributions lines of  red onion (Allium Ascalonicum L.) handler from farmer at Kintamani District, namely line Line I (Farmer?retailer), Line II (Farme?collector?retailer), Line III (Farme?collector?retailer), and lines IV (Farme?collector?traders?retailer). Identification Postharvest handling factors at the farm level include cleaning and sorting. At the collecting level include transportation and storage, at the merchant level includes cleaning, sorting and transport, and at the retailer level includes cleaning, sorting and display. Impact on Postharvest loss on the farmers level is at the sorting reaches 6% (significant). At the sorter level the collector reaches 5%, at the sorter seller level reaches 5%, and at the sorter retailer level reaches 6% (significant). Keywords : CSAM application, onion, aplication